2015
DOI: 10.1097/jom.0000000000000554
|View full text |Cite
|
Sign up to set email alerts
|

Injury and Illness Data for Illinois Mining Industry Employees, 1990 to 2012

Abstract: Systemic injuries are important drivers for TWC in miners in terms of median compensation and TTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…A majority of mining-related injuries and illnesses that were severe enough to result in a WC claim were not captured by MSHA 13 . The MSHA data underreports mining related illnesses and chronic injuries, 10,31,32 which is likely also true for the NCCI data. Table 9 supports this statement as respiratory diseases, nervous system diseases, and cumulative disorders (including carpal tunnel syndrome) had higher percents of total NCCI claims than the same categories had as percents of total MSHA cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A majority of mining-related injuries and illnesses that were severe enough to result in a WC claim were not captured by MSHA 13 . The MSHA data underreports mining related illnesses and chronic injuries, 10,31,32 which is likely also true for the NCCI data. Table 9 supports this statement as respiratory diseases, nervous system diseases, and cumulative disorders (including carpal tunnel syndrome) had higher percents of total NCCI claims than the same categories had as percents of total MSHA cases.…”
Section: Discussionmentioning
confidence: 99%
“…9 Occupational injuries and illnesses are underreported in the United States, including the US mining sector. [10][11][12] A study from Illinois found that 66% of mining workers' compensation (WC) claims were not reported in the Mine Safety and Health Administration (MSHA) injury data, 13 and an MSHA analysis of injuries in Kentucky and California from 2000 to 2012 estimated that between 23% and 46% of mining injuries were unreported. 14 This underestimation affects the way decision makers view investments in research and worker protection, which in turn has a substantial impact on national welfare and public health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Employees of mining equipment supply companies were excluded. This selection process is described in a recent publication by our research team . Finally, all cases with a status of dismissed were excluded ( N = 288).…”
Section: Methodsmentioning
confidence: 99%